A novel insight into the underlying mechanism of Baihe Dihuang Tang improving the state of psychological suboptimal health subjects obtained from plasma metabolic profiles and network analysis - Tian, Jun-sheng; Meng, Yan; Wu, Yan-fei; Zhao, Lei; Xiang, Huan; Jia, Jin-ping; Qin, Xue-mei (Journal of pharmaceutical and biomedical analysis, 2019)
•The metabolites in subjects of PSHS were determined and identified with the combination of GC-MS and LC-MS technology platform.•The “metabolites-pathways-genes-targets-components” network was constructed by combining the experiments and network prediction.•Discovery of potential targets for BDT intervention in the subjects with PSHS were analyzed. Psychological suboptimal health state (PSHS), a subtype of suboptimal health status (SHS), seriously threatens the physical and mental health of human beings. Baihe Dihuang Tang (BDT), a traditional Chinese medicine prescription, has been used to improve PSHS in clinical and achieve significant efficacy for a long time. Exploring of the underlying mechanism of BDT improving the state of PSHS is of significant importance. In the present work, all subjects were screened in strict accordance with inclusion and exclusion criteria. the UHPLC-Q Exactive Orbitrap-MS and Trace GC-PolarisQ Mass were performed to analyze the metabolic features of BDT improving the state of PSHS. Combined with the experimental results of metabolomics and the predicted results of network pharmacology, the metabolic biological network was constructed to find the potential targets of BDT intervention on PSHS. Finally, A total of 22 differential metabolites have been identified in PSHS group. 15 plasma biomarkers were significantly regulated by BDT. The results indicated that the BDT decoction is of a significant therapeutic effect on the improvement of PSHS primarily through regulating pyruvate metabolism and phenylalanine metabolism. Moreover, it is possible for BDT to improve PSHS through the functional targets including GLO1, MAOA and MAOB, which are closely related to monoamine neurotransmitters. Here, these approaches provide a tractable, powerful tool for understanding the underlying mechanism elucidating of BDT for PSHS management.